“HYBRID WARFARE: A GEOSTRATEGIC CHALLENGE TO GEORGIA’S NATIONAL SECURITY” THE IMPORTANCE OF THE “GREEN ENERGY DEVELOPMENT AND TRANSMISSION” PROJECT FOR THE BLACK SEA BASIN AND GEORGIAS ENERGY SECURITY (Conferencea, 2024)
The events that took place in the region at the beginning of last year, in particular the hostilities that began in Eastern Europe and are still ongoing, have created new challenges for Europe, especially in the direction of importing energy resources, as market diversification in the direction of gas and electricity supply is more relevant today than ever before. All this has created a completely new reality that has created the need for alternative energy flow routes for Europe.